The economics and politics of international trade : freedom and trade - cook, gary (Routledge studies in the modern world economy ;, 1998)
The conference 1846 freedom and trade 1996 was convened to commemorate the repeal of the corn laws in 1846, an event of outstanding symbolic significance in the history of free trade.